Strategic Complements or Substitutes? The Case of Adopting Health Information Technology by U.S. Hospitals - Lin, Jianjing (The Review of Economics and Statistics, 2023)
Abstract This paper explores the adoption choice of electronic medical records by U.S. hospitals, which could exhibit strategic complements or substitutes. I find complementarities in adoption through a reduced-form analysis with instruments for unobserved market characteristics. I further develop a dynamic oligopoly model to allow for strategic timing incentives that are missing in the static model. Adopting a dominant local vendor could increase per period profits from adoption by 9.2% over choosing a marginal vendor. A counterfactual analysis suggests that an incentive program rewarding coordination, not just adoption, is more effective in achieving interoperability, especially before the widespread adoption of the technology.